2006
DOI: 10.1074/jbc.m603772200
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated Regulation of AIB1 Transcriptional Activity by Sumoylation and Phosphorylation

Abstract: AIB1, a member of the steroid receptor coactivator (SRC) family that participates in gene transcriptional activation by nuclear receptors and other transcription factors, is required for animal growth and reproductive development and implicated in breast carcinogenesis. The mechanisms underlying the AIB1 pleiotropic functions are not fully understood and neither is the regulation of its activity. Here, we showed that AIB1 was a sumoylated protein and the sumoylation attenuated the transactivation activity of A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
66
0
2

Year Published

2006
2006
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(69 citation statements)
references
References 48 publications
1
66
0
2
Order By: Relevance
“…Meanwhile, evidence for phosphorylation-obstructed SUMO modification was also found. For example, phosphorylation of the AIB1 protein by the MAPK pathway was found to be inhibitory to its SUMO modification (14). These studies highlight the important regulatory mechanism for phosphorylation-modulated SUMOylation in regulating cellular events.…”
mentioning
confidence: 92%
“…Meanwhile, evidence for phosphorylation-obstructed SUMO modification was also found. For example, phosphorylation of the AIB1 protein by the MAPK pathway was found to be inhibitory to its SUMO modification (14). These studies highlight the important regulatory mechanism for phosphorylation-modulated SUMOylation in regulating cellular events.…”
mentioning
confidence: 92%
“…It is known that NCOA3 itself can also be modified through sumoylation (46), and sumoylation can compete with ubiquitination, if such modification occurs on the same lysine residue (37,38). Indeed, in rat1 3Y1 fibroblast cells, expression of SYT and SYT-SSX1 results in increased sumoylation of Ncoa3 (Fig.…”
Section: Molecular Mechanisms Of Increased Ncoa3 Expression Induced Bmentioning
confidence: 99%
“…SUMO is also conjugated to coregulators of ERa and ERb, thereby modulating their ability to interact with the nuclear receptor and to activate transcription. [11][12][13] In addition, various components of the SUMO-conjugating machinery are upregulated in several malignancies: UBC9 in melanomas, ovarian cancer and lung adenocarcinomas, [14][15][16] the SUMO isopeptidase SENP1 in prostate cancer 17 and PIAS3 in breast, lung, prostate, colorectal and brain tumors. 18 By using MCF-7 human breast cancer cells overexpressing a dominant-negative mutant of UBC9 or wild type UBC9 in a mouse xenograft model it was shown that tumors expressing the UBC9 mutant exhibited reduced growth, whereas wild type UBC9 enhanced tumor growth.…”
mentioning
confidence: 99%